Composite material for sports protectors and preparation method of composite material

By using nylon matrix, sodium molybdate, functionalized glass fibers and carbon fluoride nanotubes in sports protective gear materials to build composite materials, the shortcomings of traditional materials in wear resistance, corrosion resistance and thermal stability are solved, and higher performance and longer service life are achieved.

CN119775771AInactive Publication Date: 2025-04-08SHANDONG VOCATIONAL COLLEGE OF LIGHT IND +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510279411.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional sports protective gear materials have shortcomings in wear resistance, corrosion resistance, lightweight and comfort, especially in high-intensity sports, and are prone to wear and corrosion, affecting athletes' safety and competitive performance.

Method used

A composite material is used, whose composition includes nylon matrix, sodium molybdate, functionalized glass fibers, carbon fluorinated carbon nanotubes, aminosilane coupling agents, silica nanoparticles and antioxidants. Molybdenum ions are introduced through grafting reactions, a three-dimensional network structure is constructed, a passivation film and a dense protective layer are formed, and multiple performance improvements are achieved.

Benefits of technology

It significantly improves the material's wear resistance, corrosion resistance and thermal stability, extends its service life, reduces replacement frequency and cost, and provides better safety and competitive performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775771A_ABST
    Figure CN119775771A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to a composite material for sports protectors and a preparation method of the composite material. The composite material for the sports protector is prepared from the following raw materials: a nylon matrix, sodium molybdate, functionalized glass fibers, fluorinated carbon nanotubes, an amino silane coupling agent, silicon dioxide nanoparticles and an antioxidant. Molybdenum ions are introduced to the surface of nylon 66 through a grafting reaction, a high-hardness molybdenum-based compound layer is formed, the friction coefficient is reduced, the interface bonding strength is improved, a three-dimensional network structure is constructed by the fluorinated carbon nanotubes, friction energy is absorbed, crack propagation is inhibited, hydrophobicity is enhanced, swelling caused by water absorption is prevented, and the wear resistance is improved. A 3-aminopropyltriethoxysilane coupling agent is used for connecting SiO2 and a matrix, micro-cracks are covered, the wear resistance is improved, glass fibers reinforce rigid support of the matrix, and a hard support and soft lubrication structure is formed in cooperation with the molybdenum-based lubrication effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a composite material for sports protective gear and a preparation method thereof. Background Art

[0002] In the field of sports, the design and manufacture of protective gear is crucial to the safety of athletes. With the continuous improvement of sports level and the increasing complexity of the competitive environment, the requirements for the performance of protective gear are also gradually increasing. As an important equipment for athletes to protect their bodies from injury during training and competition, the performance of sports protective gear is directly related to the safety and competitive performance of athletes. However, although traditional protective gear materials such as leather, rubber and ordinary plastics have certain effects on basic protection performance, they have obvious deficiencies in wear resistance, corrosion resistance, lightweight and comfort. For example, in high-impact sports such as basketball, football and rugby, athletes often face severe collisions and frictions, which requires protective gear to have not only excellent cushioning performance, but also excellent wear resistance and corrosion resistance to ensure that it can provide lasting and effective protection in various harsh environments. Composite materials have become an ideal choice for sports equipment manufacturing due to their unique combination of properties. Among them, carbon fiber composite materials (CFRP) are known for their extremely low density and ultra-high strength and are widely used in high-performance sports equipment. However, despite the significant advantages of carbon fiber composite materials, their durability under long-term exposure to the natural environment (such as direct sunlight and the influence of chemicals) still has certain limitations. In addition, aramid composite materials, as a high-performance synthetic fiber material, have extremely high strength, excellent heat resistance and chemical corrosion resistance, but aramid materials also have problems such as high processing costs and insufficient durability under extreme conditions, which limit their further promotion. In actual use, sports protective gear needs to withstand friction and impact frequently, especially in high-intensity sports. The insufficient wear resistance of traditional materials can easily lead to premature wear of protective gear, which not only shortens the service life, but also increases the replacement frequency and cost. At the same time, after long-term contact with sweat, rain or other corrosive substances, traditional materials are prone to corrosion, resulting in decreased performance, and may even cause irritation or damage to the athlete's skin. Therefore, in response to the above problems, it is extremely necessary to develop a composite material that has excellent wear resistance, corrosion resistance and thermal stability. Summary of the invention

[0003] In view of the defects of the prior art, the object of the present invention is to provide a composite material for sports protective gear and a preparation method thereof.

[0004] The technical effect described in the present invention is achieved through the following technical scheme: a composite material for sports protective gear, which comprises the following raw materials: nylon matrix, sodium molybdate, functionalized glass fiber, fluorinated carbon nanotubes, aminosilane coupling agent, silica nanoparticles and antioxidant.

[0005] Preferably, the nylon matrix is ​​nylon 66.

[0006] Preferably, the specific preparation steps of the functionalized glass fiber are as follows: S1: The glass fiber is completely immersed in anhydrous ethanol, ultrasonically treated at 60W for 20 to 30 minutes, washed with deionized water, and dried at 80°C for 2 hours to obtain pretreated glass fiber; the pretreated glass fiber is immersed in a 10wt% hydrochloric acid solution, soaked for 1 hour, and dried at 80°C for 2 hours to obtain activated glass fiber; S2: immersing the activated glass fiber prepared in step S1 into a 30-50wt% nitric acid solution, stirring at room temperature for 1-2 hours, washing with deionized water, vacuum drying at 80°C for 2-4 hours, and heat treating at 120°C for 1-2 hours to obtain functionalized glass fiber; Preferably, the specific preparation steps of the fluorinated carbon nanotubes are as follows: S101: immersing the carbon nanotubes in concentrated nitric acid, ultrasonically treating them at 60W for 2 hours, washing them with deionized water until they are neutral, and heat treating them at 400-500°C for 1-2 hours to obtain pretreated carbon nanotubes; S102: adding the pretreated carbon nanotubes prepared in step S101 into a reaction furnace, maintaining a nitrogen atmosphere to exclude air, then introducing fluorine gas, controlling the gas flow rate to 10-50 mL / min, controlling the temperature to 200-400° C., reacting for 1-4 hours, and continuing to introduce nitrogen after the reaction to cool to room temperature, repeatedly washing with anhydrous ethanol for 3 times, and vacuum drying at 60-80° C. for 12 hours to obtain fluorinated carbon nanotubes; Preferably, the aminosilane coupling agent is 3-aminopropyltriethoxysilane.

[0007] Preferably, the antioxidant is any one of 2,6-di-tert-butyl-4-methylphenol, Irganox 1010 and N-phenyl-α-naphthylamine.

[0008] Preferably, another aspect of the present invention is to provide a method for preparing a composite material for sports protective gear, and the specific preparation steps are as follows: S201: dissolving sodium molybdate in deionized water, adding hydrochloric acid to adjust the pH to 3-4, and obtaining a 10-15wt% sodium molybdate solution; immersing nylon in the sodium molybdate solution, controlling the temperature to 60-80°C, stirring the reaction for 2-6 hours, and then heat treating at 120-150°C for 1-2 hours to obtain grafted nylon; S202: immersing the pretreated nylon prepared in step S201 into 30 wt% hydrogen peroxide, stirring at 60° C. for 1 to 2 hours, washing with deionized water, and drying at 80° C. for 2 hours to obtain activated nylon; S203: adding fluorinated carbon nanotubes to anhydrous ethanol, dispersing them uniformly by ultrasonic treatment, then adding aminosilane coupling agent, and ultrasonic treatment at 100W for 2-3 hours to obtain a fluorinated carbon nanotube suspension; immersing functionalized glass fiber in 1-2wt% aminosilane coupling agent solution, stirring for 2-3 hours, filtering, and vacuum drying at 80°C for 2 hours to obtain pretreated glass fiber; adding silica nanoparticles to 2-5wt% aminosilane coupling agent solution, dispersing them uniformly by ultrasonic treatment, and then stirring at 60°C for 2-3 hours to obtain a SiO2 composite suspension; S204: adding the antioxidant, the activated nylon prepared in step S202, the fluorinated carbon nanotube suspension prepared in step S203, the pretreated glass fiber and the SiO2 composite suspension into a high-speed mixer, mixing at 1000-1500 rpm for 10-15 minutes, then melt-blending and extruding, and drying at 80° C. for 4-6 hours to obtain a composite material for sports protective gear; Preferably, in step S203, the aminosilane coupling agent solution is prepared by dissolving the aminosilane coupling agent in anhydrous ethanol; the ratio of the amount of the fluorinated carbon nanotubes, anhydrous ethanol and the aminosilane coupling agent is 1 g: 200-400 mL: 0.05-0.1 mL; the ratio of the amount of the silicon dioxide nanoparticles and the aminosilane coupling agent solution is 0.3-0.5 g: 100 mL; Preferably, in step S204, the ratio of the amount of the activated nylon, the fluorinated carbon nanotube suspension, the pretreated glass fiber and the SiO2 composite suspension is 14g:300-600mL:3-4.5g:400-500mL; the amount of the antioxidant is 0.5-0.8% of the mass of the activated nylon; Preferably, in step S204, the parameters of the melt blending extrusion are: 220-230° C. in the feeding zone, 240-250° C. in the melting zone, 230-240° C. in the extrusion zone, 8-12 min, and a rotation speed of 400-500 rpm.

[0009] The beneficial effects of the present invention are as follows: The present invention introduces evenly distributed molybdenum ions on the surface of nylon 66 through a grafting reaction to form a high-hardness molybdenum-based compound layer, which reduces the friction coefficient through the solid lubrication effect during the friction process. Under the action of dynamic stress, the surface molybdenum ions form stable chemical bonds with the polar groups (such as amino groups and carboxyl groups) of nylon 66, significantly improving the interfacial bonding strength and effectively inhibiting the generation of wear debris. At the same time, fluorinated carbon nanotubes (F-CNTs) build a three-dimensional network structure in the matrix with their high strength and toughness, absorb friction energy through mechanical interlocking, and cooperate with the molybdenum-based compound layer to disperse local molecular chain stress, thereby inhibiting crack propagation. The CF bonds grafted on the surface of fluorinated carbon nanotubes significantly enhance hydrophobicity, effectively block water molecules from penetrating into the matrix, and inhibit water absorption and swelling of nylon 66; at the same time, the electronegativity of fluorine atoms can passivate the active sites on the surface of carbon nanotubes, reducing the interaction with corrosive media (such as Cl ⁻ ) chemical adsorption tendency. Fluorine atoms on the surface of fluorinated carbon nanotubes can release fluorine-containing free radicals during friction, and react with the molybdenum-based compound layer to generate molybdenum fluoride with low shear strength, realizing the dual mechanism of "in-situ solid lubrication + chemical friction reduction". In addition, the hydrophobic network of fluorinated carbon nanotubes and the molybdenum oxide passivation film form a "physical barrier + chemical passivation" hydrophobic-hydrophobic interface, and the dual protection super-hydrophobic property extends the diffusion path of the corrosive medium; fluorine atoms combine with the oxygen vacancies of molybdenum oxide to improve the density of the passivation film.

[0010] The present invention introduces active groups such as hydroxyl groups on the surface of glass fiber through oxidation treatment, significantly enhancing its interfacial compatibility with nylon 66 matrix. The rigid support of glass fiber and the lubricating effect of molybdenum-based compounds synergistically form a "hard support + soft lubrication" composite wear-resistant structure, reducing the risk of shear failure at the fiber-matrix interface. 3-aminopropyltriethoxysilane is used as a coupling agent, and its siloxane bond can bridge the silica particles (SiO2) and the matrix to form a dense protective layer covering the surface microcracks, which not only reduces the scratch probability of external hard particles, but also improves the interface wear resistance through chemical bonding. In terms of corrosion protection, molybdenum ions on the surface of the material generate a continuous and dense molybdenum oxide passivation film through redox reaction, which effectively blocks the penetration of corrosive media. The hydrophobic properties of fluorinated carbon nanotubes can inhibit water absorption by nylon 66 matrix, and its insulating properties block the electron migration path of electrochemical corrosion. Combined with the "maze effect" generated by the network structure, the diffusion path of the corrosive medium is extended together, effectively improving corrosion resistance. The SiO2 and KH550 composite layer forms a physical-chemical dual barrier protection system through nanoparticle filling of micropores and chemical anchoring. The silica nanoparticles provide physical barriers, while the amino reaction of KH-550 enhances the interface bonding and synergistically inhibits local corrosion. In terms of thermal stability system, the rigid skeleton of glass fiber and the nano-constraint effect of carbon nanotubes synergistically inhibit the thermal motion of molecular chains, and the three-dimensional heat transfer network formed effectively disperses local thermal effects. Molybdenum-based compounds maintain structural stability at high temperatures, and their free radical capture ability delays the thermal decomposition of the matrix; the SiO2 and KH550 composite layer reduces oxygen contact through high-temperature oxidation tolerance, further ensuring the reliability of the material under extreme conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0012] Figure 1 It is a corrosion resistance test result diagram of the nylon composite material samples for sports protective gear prepared in Example 2 of the present invention and Comparative Examples 1 to 4 in an acidic solution; Figure 2 It is a corrosion resistance test result diagram of the nylon composite material samples for sports protective gear prepared in Example 2 of the present invention and Comparative Examples 1 to 4 in a salt solution; Figure 3 1 is a graph showing the wear resistance test results of the nylon composite materials for sports protective gear prepared in Example 2 of the present invention and Comparative Examples 1 to 5; Figure 4 It is a graph showing the thermal stability test results of the nylon composite materials for sports protective gear prepared in Example 2 of the present invention and Comparative Examples 3 and 5. DETAILED DESCRIPTION

[0013] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that, unless otherwise specified, the raw materials involved in the present invention are purchased through conventional commercial channels.

[0014] Example 1: A composite material for sports protective gear, comprising the following raw materials: a nylon matrix, sodium molybdate, functionalized glass fiber, fluorinated carbon nanotubes, an aminosilane coupling agent, silicon dioxide nanoparticles and an antioxidant.

[0015] The specific preparation steps of functionalized glass fiber are as follows: S1: 10 g of glass fiber was completely immersed in 200 mL of anhydrous ethanol, ultrasonically treated at 60 W for 20 min, washed with deionized water, and dried at 80 ° C for 2 h to obtain pretreated glass fiber; 10 g of pretreated glass fiber was immersed in 200 mL of 10 wt% hydrochloric acid solution, soaked for 1 h, and dried at 80 ° C for 2 h to obtain activated glass fiber; S2: immersing 10 g of the activated glass fiber prepared in step S1 into 200 mL of 30 wt% nitric acid solution, stirring at room temperature for 1 h, washing with deionized water, vacuum drying at 80° C. for 2 h, and heat treating at 120° C. for 1 h to obtain functionalized glass fiber; The specific preparation steps of fluorinated carbon nanotubes are as follows: S101: 1 g of carbon nanotubes were immersed in 200 mL of concentrated nitric acid, ultrasonically treated at 60 W for 2 h, washed with deionized water until neutral, and heat treated at 400 °C for 2 h to obtain pretreated carbon nanotubes; S102: Add 1 g of pretreated carbon nanotubes prepared in step S101 into a reaction furnace, maintain a nitrogen atmosphere to exclude air, then introduce fluorine gas, control the gas flow rate to 10 mL / min, control the temperature to 200°C, react for 4 hours, continue to introduce nitrogen after the reaction is completed, cool to room temperature, repeat washing with anhydrous ethanol for 3 times, and vacuum dry at 60°C for 12 hours to obtain fluorinated carbon nanotubes; The specific preparation steps of composite materials for sports protective gear are as follows: S201: 50 g of sodium molybdate was dissolved in 500 mL of deionized water, and hydrochloric acid was added to adjust the pH to 4 to obtain a 10 wt% sodium molybdate solution; 20 g of nylon was immersed in 500 mL of the sodium molybdate solution, the temperature was controlled at 60° C., the reaction was stirred for 6 h, and then heat-treated at 120° C. for 2 h to obtain grafted nylon; S202: immersing 20 g of the pretreated nylon prepared in step S201 into 500 mL of 30 wt% hydrogen peroxide, stirring at 60° C. for 1 h, washing with deionized water, and drying at 80° C. for 2 h to obtain activated nylon; S203: 2 g of fluorinated carbon nanotubes were added to 400 mL of anhydrous ethanol, and the mixture was dispersed evenly by ultrasonic treatment. Then, 0.1 mL of 3-aminopropyltriethoxysilane was added, and the mixture was ultrasonically treated at 100 W for 2 h to obtain a fluorinated carbon nanotube suspension. 5 g of functionalized glass fiber was immersed in 200 mL of 1 wt% 3-aminopropyltriethoxysilane solution prepared in anhydrous ethanol, and the mixture was stirred for 2 h. The mixture was filtered and vacuum dried at 80 ° C for 2 h to obtain pretreated glass fiber. 1.5 g of silica nanoparticles were added to 500 mL of 2 wt% 3-aminopropyltriethoxysilane solution prepared in anhydrous ethanol, and the mixture was dispersed evenly by ultrasonic treatment. Then, the mixture was stirred at 60 ° C for 2 h to obtain a SiO2 composite suspension. S204: Add 0.07 g of N-phenyl-α-naphthylamine, 14 g of activated nylon prepared in step S202, 300 mL of fluorinated carbon nanotube suspension prepared in step S203, 3 g of pretreated glass fiber and 400 mL of SiO2 composite suspension into a high-speed mixer, mix at 1000 rpm for 15 min, and then melt-blend and extrude. The parameters are set at 220° C. in the feeding zone, 240° C. in the melting zone, 230° C. in the extrusion zone, 8 min in the time, 400 rpm in the rotation speed, and dried at 80° C. for 4 h to obtain a composite material for sports protective gear.

[0016] Example 2: A composite material for sports protective gear, comprising the following raw materials: nylon matrix, sodium molybdate, functionalized glass fiber, fluorinated carbon nanotubes, aminosilane coupling agent, silica nanoparticles and antioxidant.

[0017] The specific preparation steps of functionalized glass fiber are as follows: S1: 10 g of glass fiber was completely immersed in 200 mL of anhydrous ethanol, ultrasonically treated at 60 W for 25 min, washed with deionized water, and dried at 80 ° C for 2 h to obtain pretreated glass fiber; 10 g of pretreated glass fiber was immersed in 200 mL of 10 wt% hydrochloric acid solution, soaked for 1 h, and dried at 80 ° C for 2 h to obtain activated glass fiber; S2: immersing 10 g of the activated glass fiber prepared in step S1 into 200 mL of 40 wt% nitric acid solution, stirring at room temperature for 1.5 h, washing with deionized water, vacuum drying at 80° C. for 3 h, and heat treating at 120° C. for 1.5 h to obtain functionalized glass fiber; The specific preparation steps of fluorinated carbon nanotubes are as follows: S101: 1 g of carbon nanotubes were immersed in 200 mL of concentrated nitric acid, subjected to 60 W ultrasonic treatment for 2 h, washed with deionized water until neutral, and heat treated at 450 ° C for 1.5 h to obtain pretreated carbon nanotubes; S102: Add 1 g of pretreated carbon nanotubes prepared in step S101 into a reaction furnace, maintain a nitrogen atmosphere to exclude air, then introduce fluorine gas, control the gas flow rate to 35 mL / min, control the temperature to 350°C, and react for 3 hours. After the reaction is completed, continue to introduce nitrogen to cool to room temperature, repeat washing with anhydrous ethanol for 3 times, and vacuum dry at 70°C for 12 hours to obtain fluorinated carbon nanotubes; The specific preparation steps of composite materials for sports protective gear are as follows: S201: 60 g of sodium molybdate was dissolved in 500 mL of deionized water, and hydrochloric acid was added to adjust the pH to 3.5 to obtain a 12 wt% sodium molybdate solution; 20 g of nylon was immersed in 500 mL of the sodium molybdate solution, the temperature was controlled at 70°C, the reaction was stirred for 5 hours, and then heat-treated at 150°C for 1.5 hours to obtain grafted nylon; S202: immersing 20 g of the pretreated nylon prepared in step S201 into 500 mL of 30 wt% hydrogen peroxide, stirring at 60° C. for 1.5 h, washing with deionized water, and drying at 80° C. for 2 h to obtain activated nylon; S203: 2g of fluorinated carbon nanotubes were added to 600mL of anhydrous ethanol, and the mixture was dispersed evenly by ultrasonic treatment. Then, 0.2mL of 3-aminopropyltriethoxysilane was added, and the mixture was ultrasonically treated at 100W for 2.5h to obtain a fluorinated carbon nanotube suspension. 5g of functionalized glass fiber was immersed in 200mL of 1.5wt% 3-aminopropyltriethoxysilane solution prepared in anhydrous ethanol, and the mixture was stirred for 2.5h, filtered, and vacuum dried at 80°C for 2h to obtain pretreated glass fiber. 2.5g of silica nanoparticles were added to 500mL of 4wt% 3-aminopropyltriethoxysilane solution prepared in anhydrous ethanol, and the mixture was dispersed evenly by ultrasonic treatment. Then, the mixture was stirred at 60°C for 2.5h to obtain a SiO2 composite suspension. S204: 0.11 g of Irganox 1010, 14 g of activated nylon prepared in step S202, 600 mL of fluorinated carbon nanotube suspension prepared in step S203, 4 g of pretreated glass fiber and 500 mL of SiO2 composite suspension were added to a high-speed mixer, mixed at 1500 rpm for 12 min, and then melt-blended and extruded. The parameters were set to 225° C. in the feeding zone, 245° C. in the melting zone, 235° C. in the extrusion zone, 10 min in the time, 500 rpm in the rotation speed, and dried at 80° C. for 6 h to obtain a composite material for sports protective gear.

[0018] Example 3: A composite material for sports protective gear, comprising the following raw materials: nylon matrix, sodium molybdate, functionalized glass fiber, fluorinated carbon nanotubes, aminosilane coupling agent, silica nanoparticles and antioxidant.

[0019] The specific preparation steps of functionalized glass fiber are as follows: S1: 10 g of glass fiber was completely immersed in 200 mL of anhydrous ethanol, ultrasonically treated at 60 W for 30 min, washed with deionized water, and dried at 80 ° C for 2 h to obtain pretreated glass fiber; 10 g of pretreated glass fiber was immersed in 200 mL of 10 wt% hydrochloric acid solution, soaked for 1 h, and dried at 80 ° C for 2 h to obtain activated glass fiber; S2: immersing 10 g of the activated glass fiber prepared in step S1 into 200 mL of 50 wt% nitric acid solution, stirring at room temperature for 2 h, washing with deionized water, vacuum drying at 80° C. for 4 h, and heat treating at 120° C. for 2 h to obtain functionalized glass fiber; The specific preparation steps of fluorinated carbon nanotubes are as follows: S101: 1 g of carbon nanotubes were immersed in 200 mL of concentrated nitric acid, ultrasonically treated at 60 W for 2 h, washed with deionized water until neutral, and heat treated at 500 °C for 1 h to obtain pretreated carbon nanotubes; S102: Add 1 g of the pretreated carbon nanotubes prepared in step S101 into the reaction furnace, maintain a nitrogen atmosphere to exclude air, then introduce fluorine gas, control the gas flow rate to 50 mL / min, control the temperature to 400°C, react for 1 hour, continue to introduce nitrogen after the reaction is completed, cool to room temperature, repeat washing with anhydrous ethanol for 3 times, and vacuum dry at 80°C for 12 hours to obtain fluorinated carbon nanotubes; The specific preparation steps of composite materials for sports protective gear are as follows: S201: 75 g of sodium molybdate was dissolved in 500 mL of deionized water, and hydrochloric acid was added to adjust the pH to 3 to obtain a 15 wt% sodium molybdate solution; 20 g of nylon was immersed in 500 mL of the sodium molybdate solution, the temperature was controlled at 80° C., the reaction was stirred for 2 h, and then heat-treated at 140° C. for 1 h to obtain grafted nylon; S202: immersing 20 g of the pretreated nylon prepared in step S201 into 500 mL of 30 wt% hydrogen peroxide, stirring at 60° C. for 2 h, washing with deionized water, and drying at 80° C. for 2 h to obtain activated nylon; S203: 2 g of fluorinated carbon nanotubes were added to 800 mL of anhydrous ethanol, and the mixture was dispersed evenly by ultrasonic treatment. Then, 0.16 g of 3-aminopropyltriethoxysilane was added, and the mixture was ultrasonically treated at 100 W for 3 h to obtain a fluorinated carbon nanotube suspension. 5 g of functionalized glass fiber was immersed in 200 mL of 2 wt% 3-aminopropyltriethoxysilane solution prepared in anhydrous ethanol, and the mixture was stirred for 3 h, filtered, and vacuum dried at 80 ° C for 2 h to obtain pretreated glass fiber. 2.3 g of silica nanoparticles were added to 500 mL of 5 wt% 3-aminopropyltriethoxysilane solution prepared in anhydrous ethanol, and the mixture was dispersed evenly by ultrasonic treatment. Then, the mixture was stirred at 60 ° C for 3 h to obtain a SiO2 composite suspension. S204: Add 0.112 g of 2,6-di-tert-butyl-4-methylphenol, 14 g of activated nylon prepared in step S202, 500 mL of fluorinated carbon nanotube suspension prepared in step S203, 4.5 g of pretreated glass fiber and 480 mL of SiO2 composite suspension into a high-speed mixer, mix at 1400 rpm for 10 min, and then melt-blend and extrude. The parameters are set at 230°C in the feeding zone, 250°C in the melting zone, 240°C in the extrusion zone, 12 min in the time, 450 rpm in the rotation speed, and dried at 80°C for 5 h to obtain a composite material for sports protective gear.

[0020] Comparative Example 1: The operation of Comparative Example 1 is substantially the same as that of Example 2, except that sodium molybdate is not used in Comparative Example 1.

[0021] Comparative Example 2: The operation of Comparative Example 2 is substantially the same as that of Example 2, except that 3-glycidyloxypropyltrimethoxysilane is used in Comparative Example 2 to replace 3-aminopropyltriethoxysilane.

[0022] Comparative Example 3: The operation of Comparative Example 3 is substantially the same as that of Example 2, except that carbon nanotubes are used in Comparative Example 3 to replace fluorinated carbon nanotubes.

[0023] Comparative Example 4: The operation of Comparative Example 4 is substantially the same as that of Example 2, except that no fluorinated carbon nanotubes are used in Comparative Example 4.

[0024] Comparative Example 5: The operation of Comparative Example 5 is substantially the same as that of Example 2, except that no functionalized glass fiber is used in Comparative Example 5.

[0025] Performance Test: Mechanical strength test: The nylon composite material samples for sports protective gear prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were subjected to multiple cyclic tensile strength, flexural strength and impact strength tests using a universal material testing machine. The results are shown in Table 1 below.

[0026] Table 1. Mechanical strength test results of nylon composite materials for sports protective gear

[0027] It can be seen from the results in Table 1 that the nylon composite material prepared by the present invention utilizes the synergistic effect of multiple substances to achieve a significant improvement in mechanical properties; from the results of Comparative Example 1 and Example 2, it can be seen that the molybdenum ions form chemical bonds with the polar groups of nylon 66, which significantly improves the interface bonding strength. After the loss of sodium molybdate, the interface bonding strength is significantly reduced, the stress transfer efficiency is reduced, and the mechanical strength is significantly reduced; from the results of Comparative Example 2 and Example 2, it can be seen that the amino group of KH550 forms hydrogen bonds and covalent bonds with the carboxyl group of nylon 66, while the epoxy group of KH560 has low reactivity with the polar group of nylon 66, resulting in a weakened interface bonding force between SiO2 particles and the matrix, which in turn leads to a significant decrease in overall mechanical properties. ; From the results of Comparative Example 3 and Example 2, it can be seen that the surface of ordinary carbon nanotubes is inert, and the mechanical interlocking effect with the nylon 66 matrix is ​​weak, and an effective three-dimensional network cannot be constructed, and the mechanical properties are affected to a certain extent; From the results of Comparative Example 4 and Example 2, it can be seen that the high-strength-toughness network of fluorinated carbon nanotubes is the core carrier of stress dispersion, and its absence leads to local molecular chain stress concentration, accelerated crack propagation rate, and a significant decrease in mechanical strength; From the results of Comparative Example 5 and Example 2, it can be seen that the unfunctionalized glass fiber has poor compatibility with the matrix interface, and the rigid skeleton cannot form a composite structure of hard support and soft lubrication with the molybdenum-based lubricating layer. The lack of a rigid support structure leads to a significant decrease in mechanical strength.

[0028] Corrosion resistance test: The nylon composite material samples for sports protective gear prepared in Example 2 and Comparative Examples 1 to 4 were immersed in 98wt% concentrated sulfuric acid solution and 3.5% NaCl solution for 30 days, and then the weight loss was tested on the 3rd, 7th, 14th and 30th days respectively. The weight loss results are shown in FIG. Figure 1 and Figure 2 shown.

[0029] Depend on Figure 1 and Figure 2The results show that the nylon composite material prepared by the present invention has excellent corrosion resistance and can be effectively used for a long time in a relatively extreme environment; from the results of Comparative Example 1 and Example 2, it can be seen that the molybdenum ions generate a continuous and dense molybdenum oxide passivation film through redox reaction, which effectively blocks the penetration of corrosive media. After the sodium molybdate is missing, an effective passivation film cannot be formed, and the corrosive media easily penetrate into the matrix. The chemical bonding between the molybdenum ions and the polar groups of nylon 66 is missing, and the interface bonding strength is weakened, resulting in the corrosive medium easily penetrating from the interface, and the corrosion resistance is significantly reduced; from the results of Comparative Example 2 and Example 2, it can be seen that the amino group of KH-550 forms a bond with the molybdenum ions and the fluorinated carbon nanotubes to enhance the interface bonding strength. After being replaced with epoxy silane, the interface chemical bonding ability is weakened. The density of the protective layer decreases significantly, the corrosive medium is easy to penetrate, and the corrosion resistance decreases significantly; from the results of Comparative Example 3 and Example 2, it can be seen that the CF bonds grafted on the surface of the fluorinated carbon nanotubes significantly enhance the hydrophobicity and effectively block the water molecules from penetrating into the matrix. Ordinary carbon nanotubes lack hydrophobicity, which causes the matrix to absorb water and swell, the corrosive medium is easy to penetrate, and the corrosion resistance decreases significantly; from the results of Comparative Example 4 and Example 2, it can be seen that the three-dimensional hydrophobic network constructed by the fluorinated carbon nanotubes effectively blocks the penetration of water molecules and corrosive media. After the fluorinated carbon nanotubes are missing, the corrosive medium is easy to penetrate into the matrix; and the fluorinated carbon nanotubes disperse stress through mechanical interlocking and interface enhancement effect to inhibit crack propagation. After their absence, stress concentration is aggravated, and the corrosive medium is easy to penetrate from the microcracks, which leads to a significant decrease in corrosion resistance.

[0030] Wear resistance test: The nylon composite material samples for sports protective gear prepared in Example 2 and Comparative Examples 1 to 5 were polished at 60 rpm using a 600 g CS-10 grinding wheel for 500 and 1000 turns, and the weight change before and after the test was measured. The wear loss = (weight before test - weight after test) / weight before test × 100%. The results are as follows: Figure 3 shown.

[0031] Depend on Figure 3As can be seen from the results, the nylon composite material prepared by the present invention has excellent wear resistance through the synergistic effect of multiple substances; from the results of Comparative Example 1 and Example 2, it can be seen that the lack of the molybdenum-based compound layer cannot form an effective solid lubrication and interface enhancement effect, the friction coefficient increases, the wear is aggravated, and the wear resistance decreases significantly; from the results of Comparative Example 2 and Example 2, it can be seen that the interface bonding ability of epoxy silane is weak, resulting in a decrease in the density of the protective layer, and the wear resistance is affected to a certain extent; from the results of Comparative Example 3 and Example 2, it can be seen that ordinary carbon nanotubes lack the hydrophobicity and tribochemical activity of CF bonds, cannot effectively reduce the friction coefficient and inhibit crack propagation, and the wear resistance decreases significantly; from the results of Comparative Example 4 and Example 2, it can be seen that the lack of the three-dimensional network structure and interface enhancement effect of F-CNTs, the stress dispersion ability decreases, the wear is aggravated, and the long-term wear resistance decreases significantly; from the results of Comparative Example 5 and Example 2, it can be seen that the lack of the rigid support of the functionalized glass fiber weakens the fiber-matrix interface bonding, aggravates the wear, and the wear resistance decreases significantly.

[0032] Thermal stability test: The nylon composite material samples for sports protective gear prepared in Example 2 and Comparative Examples 3 and 5 were placed in a thermogravimetric analyzer, and the temperature was raised to 600°C at a rate of 10°C / min. The weight loss percentage of the nylon composite material at 200°C, 300°C, 400°C, 500°C and 600°C was recorded. The results are as follows: Figure 4 shown.

[0033] Depend on Figure 4 The results show that the nylon composite material prepared by the present invention achieves excellent thermal stability through the synergistic effect of multiple materials, and obvious thermal decomposition begins to occur above 400°C; from the results of Comparative Example 3 and Example 2, it can be seen that although carbon nanotubes have good mechanical properties, they are not as stable as fluorinated carbon nanotubes at high temperatures, and lack the synergistic effect of fluorinated carbon nanotubes, the composite material decomposes faster at high temperatures and has poor thermal stability; from the results of Comparative Example 5 and Example 2, it can be seen that the lack of functionalized glass fiber to provide rigid support and enhance the thermal stability of the composite material, and the lack of synergy with other materials, resulting in significant decomposition of the composite material at high temperatures and poor thermal stability.

[0034] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A composite material for sports protective gear, characterized in that: The composition includes the following raw materials: nylon matrix, sodium molybdate, functionalized glass fiber, fluorinated carbon nanotube, aminosilane coupling agent, silicon dioxide nanoparticles and antioxidant; The specific preparation steps of the functionalized glass fiber are as follows: S1: completely immersing the glass fiber in anhydrous ethanol, ultrasonically treating it, washing it with deionized water, and drying it to obtain pretreated glass fiber; immersing the pretreated glass fiber in a hydrochloric acid solution, and after the immersion treatment is completed, drying it to obtain activated glass fiber; S2: immersing the activated glass fiber prepared in step S1 into a nitric acid solution, stirring at room temperature, washing with deionized water, vacuum drying, and then heat treating to obtain a functionalized glass fiber.

2. A composite material for sports protective gear according to claim 1, characterized in that: The specific preparation steps of the fluorinated carbon nanotubes are as follows: S101: immersing the carbon nanotubes in concentrated nitric acid, ultrasonically treating, washing with deionized water until neutral, and heat treating to obtain pretreated carbon nanotubes; S102: Add the pretreated carbon nanotubes prepared in step S101 into the reaction furnace, maintain a nitrogen atmosphere to exclude air, then introduce fluorine gas, control the gas flow rate, control the temperature, continue to introduce nitrogen after the reaction is completed, cool to room temperature, repeatedly wash with anhydrous ethanol, and vacuum dry to obtain fluorinated carbon nanotubes.

3. A composite material for sports protective gear according to claim 2, characterized in that: The aminosilane coupling agent is 3-aminopropyltriethoxysilane.

4. A composite material for sports protective gear according to claim 3, characterized in that: The antioxidant is any one of 2,6-di-tert-butyl-4-methylphenol, Irganox 1010 and N-phenyl-α-naphthylamine.

5. A method for preparing the composite material for sports protective gear according to any one of claims 1 to 4, characterized in that: The specific preparation steps are as follows: S201: dissolving sodium molybdate in deionized water, adding hydrochloric acid to adjust the pH, and obtaining a sodium molybdate solution; immersing nylon in the sodium molybdate solution, controlling the temperature, stirring the reaction, and then heat treating to obtain a grafted nylon; S202: immersing the pretreated nylon prepared in step S201 into hydrogen peroxide, stirring, then washing with deionized water, and drying to obtain activated nylon; S203: adding fluorinated carbon nanotubes to anhydrous ethanol, dispersing them uniformly by ultrasonic treatment, then adding aminosilane coupling agent, and dispersing them uniformly by ultrasonic treatment to obtain a fluorinated carbon nanotube suspension; immersing functionalized glass fiber in the aminosilane coupling agent solution, stirring, filtering, and vacuum drying to obtain pretreated glass fiber; adding silicon dioxide nanoparticles to the aminosilane coupling agent solution, dispersing them uniformly by ultrasonic treatment, and then stirring to obtain a SiO2 composite suspension; S204: adding the antioxidant, the activated nylon prepared in step S202, the fluorinated carbon nanotube suspension prepared in step S203, the pretreated glass fiber and the SiO2 composite suspension into a high-speed mixer, mixing them evenly, and then melt-blending and extruding them, and drying them at low temperature to obtain a composite material for sports protective gear.

6. A method for preparing the composite material for sports protective gear according to claim 5, characterized in that: In step S203, the aminosilane coupling agent solution is prepared by dissolving the aminosilane coupling agent in anhydrous ethanol; the ratio of the fluorinated carbon nanotubes, anhydrous ethanol and the aminosilane coupling agent is 1 g: 200-400 mL: 0.05-0.1 mL.

7. A method for preparing the composite material for sports protective gear according to claim 6, characterized in that: In step S203, the ratio of the amount of the silicon dioxide nanoparticles to the amount of the aminosilane coupling agent solution is 0.3-0.5 g:100 mL.

8. A method for preparing the composite material for sports protective gear according to claim 7, characterized in that: In step S204, the ratio of the amount of activated nylon, fluorinated carbon nanotube suspension, pretreated glass fiber and SiO2 composite suspension is 14g:300-600mL:3-4.5g:400-500mL.

9. A method for preparing the composite material for sports protective gear according to claim 8, characterized in that: In step S204, the amount of the antioxidant used is 0.5-0.8% of the mass of the activated nylon.

10. A method for preparing the composite material for sports protective gear according to claim 9, characterized in that: In step S204, the parameters of the melt blending extrusion are: 220-230° C. in the feeding zone, 240-250° C. in the melting zone, 230-240° C. in the extrusion zone, 8-12 min, and a rotation speed of 400-500 rpm.

Citation Information

Patent Citations

  • Wear-resistant hydrolysis-resistant alcoholysis-resistant polyamide-based composite material, preparation method and applications thereof

    CN110776734A

  • Wear-resistant low-moisture-absorption nylon material and preparation method thereof

    CN115558287A

  • High-efficiency flame-retardant heat-conducting polyamide composite material as well as preparation method and application thereof

    CN116178946A

  • Polyamides containing manganese for light stabilization and stabilized against bleach discoloration with tungsten or molybdenum

    US3458470A